2015
DOI: 10.1590/1807-3107bor-2015.vol29.0034
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction concerning implant-supported prostheses: an observational study

Abstract: The aim of this observational study was to assess the degree of patient satisfaction toward implant-supported prostheses. A questionnaire was used with two scales (one consisting of detailed adjectival and the other of numerical responses) regarding chewing, esthetics, speaking, comfort and overall satisfaction. The scales were administered to a sample of 147 patients treated with implants and prostheses. The data were submitted to the Kappa statistic and the Chi-square test to analyze the association between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 23 publications
2
13
0
3
Order By: Relevance
“…There was a significant improvement in patients' satisfaction with aesthetics after basal implant treatment, which is in accordance with the findings of Emami et al, 40 Zitzmann and Marinello, 26 Gurgel et al, 25 and Annali et al, 31 concluding that implant treatment produced a significant improvement in patients' satisfaction with aesthetics, eating, degree of comfort, and phonetics, as well as general satisfaction.…”
Section: Discussionsupporting
confidence: 90%
“…There was a significant improvement in patients' satisfaction with aesthetics after basal implant treatment, which is in accordance with the findings of Emami et al, 40 Zitzmann and Marinello, 26 Gurgel et al, 25 and Annali et al, 31 concluding that implant treatment produced a significant improvement in patients' satisfaction with aesthetics, eating, degree of comfort, and phonetics, as well as general satisfaction.…”
Section: Discussionsupporting
confidence: 90%
“…Studies proved that individuals who were with implant-supported overdentures showed a higher level of satisfaction than those who were treated with conventional full dentures (19-21). Many studies were carried out among edentulous individuals with implant-supported overdentures or implant fixed full dentures which revealed a increased satisfaction with both therapeutic modalities (22-24).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [8,11,[23][24][25][26][27][28][29][30][31] have been conducted to evaluate patients' satisfaction with endo-osseous implantsupported prostheses using a number of parameters including mastication, aesthetics, speech, comfort, and overall satisfaction, while other studies [32][33][34][35][36][37][38][39][40] have used quality of life questionnaires such as the Oral Heath Impact Profile and the Geriatric Oral Health Assessment Index to evaluate patient satisfaction and improvement in oral-health-related quality of life.…”
Section: Introductionmentioning
confidence: 99%